The Diversification of Local Tuber Products for The Result of Gluten-Free Bakery Products - Julianti, Elisa; Ridwansyah, Ridwansyah; Yusraini, Era; Karo-Karo, Terip (Talenta Publisher Universitas Sumatera Utara, 2018)
Bakery products such as bread, cake and cookies that currently exist in the market are generally made of wheat flour. Some individuals would suffer from allergy in consuming the consumption products that contain gluten which is found in wheat flour.The purpose of this activity is to produce bakery products such as bread, cake and cookies that are gluten free by using local tuber ingredients, i.e. cassava and sweet potatoes. The activity was started with processing cassavas, sweet potatotes, orange sweet potatoes to be powder which then was processed to be various types of bakery products. The variants of products that are marketed are as many as 31 types, consisting of 28 types of bakery products such as cakes and cookies, and 3 types of wet cake products. The types of bakery products that were sold was brownies, muffin, sponge cake, cookies and snacks with various variants such as steamed, baked, flavors addition of coffee, chocolate and mocha. The bakery products are gluten-free so that they are safe to be consumed by people who are allergic to gluten. The wet cake products that were marketed were risoles, pastels and doughnuts. However, this type of cake is still wheat flour substitute product as much as 20%. This activity may support the national food security program.